Юзабилити – наука, технология, искусство - Валькман, Ю.Р.; Савченко, А,В.; Зосимов, В.В.; Булгакова, А.С. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
In the article the processes of conduct of user are analyzed and the comforts of exploitation of site are determined. Methods and principles of construction of web sites are explored.